Web Enhanced Course, Solusi Bagi Peserta Didik dalam Pemahaman Materi Perkuliahan - Andy Prasetyo Wati; Sri Handayani (Jurnal Pendidikan Ekonomi, 2020)
Cognitive abilities in students have an important role for children's success in learning because most of the activities in learning are always associated with problems of remembering and thinking. Cognitive abilities are intended so that children are able to explore the world around them through their five senses, which are collaborated with accurate analysis so that with the understanding of the knowledge they get, children can carry on their lives. In supporting the implementation of learning activities with cognitive abilities so as to produce a maximum level of understanding of lecture material, it is necessary to have an appropriate digital-based learning media so that it can collaborate between technology and cognitive abilities. One of the digital-based learning media that can be applied in supporting students' cognitive abilities is to use Web Enhanced Course (WEC). The method used in this study uses descriptive methods and linear regression. Data obtained from the results of questionnaires that have been filled out by students using simple linear regression analysis techniques. The population used in this study were students of the Faculty of Economics, Universitas Negeri Malang. The population used to measure the level of student understanding of lecture material using the Web Enhanced Course amounted to 284 students, while the sampling technique used was proportional random sampling to obtain a sample of 74 students. While the results of this study can be concluded that the use of digital learning media Web Enhanced Course has an influence on improving understanding of lecture material by students as measured using cognitive abilities. DOI: https://dx.doi.org/10.17977/um014v13i12020p061